(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, the essence, purpose, tasks of wellness technologies in modern conditions, as well as the relevance and importance of wellness technologies in physical education and sports, the functions of physical wellness in the formation of a healthy lifestyle today, and international experiences are scientifically based.